(untitled) (Research, Society and Development, 2021)
In this paper, we aimed to evaluate the perception of students at the Pernambuco School of Dentistry about the use of the Google Classroom application as a tool to support teaching-learning during the trans pandemic supplementary school period. The sample was composed of 100 students from the first to the tenth period. The online form consisted of 19 multiple choice items and the results were tabulated by the platform itself in spreadsheets (via Google Sheets), and visualized in graphs. For this, the students had access to the survey invitation through a link on the online form, which was forwarded by the researcher through messages to the WhatsApp groups of the students’ classes. Data were analyzed using descriptive statistics (mean and standard deviation, maximum and minimum value), considering as level of significance p-value ≤ 0.05 for a confidence interval of 95%. The students from the Pernambuco School of Dentistry approved the usability and interaction of the Google Classroom application as a virtual teaching-learning tool, proving to be adequate and effective when used in the subjects studied in the supplementary school period during the COVID-19 pandemic.